Phenacyl bromide as Norrish type I photoinitiator for the facile synthesis of chain-end functional PMMA and polystyrene - Kati, Mina; Cakir, Yusra Bahar; Kaya, Kerem; Kiliclar, Huseyin Cem; Kiskan, Baris (Frontiers in Materials, 2024)
Phenacyl bromide has been explored as a new Norrish Type I photoinitiator for radically polymerizing methyl methacrylate and styrene monomers. A straightforward radical photopolymerization method using UVA light for the synthesis of chain-end functional poly(methyl methacrylate) and polystyrene has been developed. The process has been refined for both bulk and solution photopolymerizations. Chain-end functionalization was demonstrated by the formation of block-copolymers of the bromine-ended homopolymers, utilized as macroinitiators, resulting in an increase in the molecular weight of the corresponding precursor, observed by gel permeation chromatography (GPC). Block copolymerization was initiated by radicals generated at the chain-ends by a halogen-atom transfer reagent, namely, dimanganese decacarbonyl (Mn2(CO)10). This simple light-induced method is promising for the additive manufacturing field such as vat photopolymerization, stereolithography, digital light processing as it yields chain-end functional materials that can be further processed.